2023
DOI: 10.3390/horticulturae9090997
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Gene Action and Identification of Heterotic Hybrids for Enhancing Yield in Field Pea

Indu Yadav,
Vijay Sharma,
Mukul Kumar
et al.

Abstract: Eight field pea parental lines and their twenty-eight F1s resulting from diallel design (excluding reciprocal) were analyzed for their combining ability and heterosis for yield and associated traits. ANOVA revealed significant variation among parents and among hybrids for days to 50% flowering, plant height, total number of pods, effective pods, seeds per pod, 100-seed weight, biological yield and seed yield; pod length also revealed significant differences among hybrids, suggesting the occurrence of considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…To know which trait or combination of traits would mitigate stress better, it is necessary to find a group of principal traits which can be obtained by principal component analysis (PCA) [ 91 ]. PCA showed that PC1 and PC2 are the important principal components as they contributed to the maximum variance in both optimal (63.62%) and stress conditions (75.62%), with an eigen value of more than one, which implies that the traits have a narrow angle in PC1 and PC2, and which may be used for indirect selection of the genotypes to mitigate the stress by creating better genetic recombinants [ 3 , 92 , 93 ]. However, most of the traits which are necessary for the survival of seedlings were showing positive correlation with H 2 O 2 and MDA in optimal condition, and had shown negative correlation in stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To know which trait or combination of traits would mitigate stress better, it is necessary to find a group of principal traits which can be obtained by principal component analysis (PCA) [ 91 ]. PCA showed that PC1 and PC2 are the important principal components as they contributed to the maximum variance in both optimal (63.62%) and stress conditions (75.62%), with an eigen value of more than one, which implies that the traits have a narrow angle in PC1 and PC2, and which may be used for indirect selection of the genotypes to mitigate the stress by creating better genetic recombinants [ 3 , 92 , 93 ]. However, most of the traits which are necessary for the survival of seedlings were showing positive correlation with H 2 O 2 and MDA in optimal condition, and had shown negative correlation in stress conditions.…”
Section: Discussionmentioning
confidence: 99%